The Effect of Learning Motivation and Academic Administration Support on Students' Academic Achievement at Lombok Business Academy - Iin Indrayani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the influence of learning motivation and academic administrative support on student academic achievement at the Lombok Business Academy. Student academic achievement is not only determined by cognitive abilities but also influenced by internal factors such as learning motivation and external factors such as institutional support. This study used a quantitative approach with an explanatory design. The study population was all active students of the Lombok Business Academy in the 2024/2025 academic year, with a sample of 222 respondents determined through a proportionate stratified random sampling technique. Data were collected using a closed questionnaire that had been tested for validity and reliability, then analyzed using multiple linear regression. The results showed that learning motivation and academic administrative support had a positive and significant effect on student academic achievement, both partially and simultaneously. Learning motivation had a more dominant influence than academic and administrative support. The coefficient of determination value of 0.482 indicates that 48.2% of the variation in student academic achievement can be explained by these two variables. This finding supports the self-determination theory, which emphasizes the importance of intrinsic motivation in academic achievement and the concept of service quality in the context of higher education. This study recommends strengthening programs to increase student learning motivation and optimizing digital-based academic administration systems to create a conducive learning environment.